Social networks and prediction markets : an experimental study - Lim, Chang Yi (2017)
The effects of social communication and social network structures are rarely discussed in prediction market and experimental asset market literature. In this paper, we seek to investigate the impact of social network structures on information acquisition, traders’ earnings and prediction market performance in double auction prediction markets. We find that Fully-connected, Circle and Periphery participants acquire significantly less information than Non-networked participants, and Core participants seem to be playing the leadership role in information acquisition in the Core- periphery treatment. Furthermore, we show that social networks have the potential to increase traders’ earnings and generally improve the performance of double auction prediction markets.